Make a Match Cooperative Learning Model: Science Learning Outcomes on Natural Resource Topic at Elementary School - Sin Algonda Porsiana; Johanes Pelamonia; Lestari Lestari (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Low science learning outcomes are often caused by the lack of active student involvement in the knowledge construction process in the classroom. This study aims to describe and analyze the improvement in science learning outcomes in the natural resource material through the implementation of the Make a Match cooperative learning model for fourth-grade students at Elementary School 2 Tiakur, Southwest Maluku Regency. The method used is Classroom Action Research (CAR) model Kemmis and McTaggart which was implemented in two cycles with 25 students. Data was collected through observation techniques, learning outcome tests, and documentation, then analyzed descriptively. The results of the study showed a significant progressive increase in each stage. In the pre-cycle stage, the average class score was only 65 with a very low classical completeness, namely 12%. The implementation of the first cycle increased the average score to 70 with a completeness level of 60%. In the second cycle, student achievement increased sharply to an average score of 79 and successfully achieved 100% classical completeness. The conclusion of this study empirically proves that the Make a Match cooperative learning model is effective in improving students' science learning outcomes comprehensively, encompassing the cognitive, psychomotor, and affective domains. This research contribution provides a practical solution for educators in island regions in optimizing student participation through interactive and enjoyable learning models.